Understanding consumers’ continuance intention toward recommendation vlogs: An exploration based on the dual-congruity theory and expectation-confirmation theory - Yang, Tiantian; Yang, Feng; Men, Jinqi (Electronic commerce research and applications, 2023)
•Exploring the impact of dual-congruity factors on consumers’ continuance intention (CI).•Integrating the expectation-confirmation theory to enhance the understanding of CI formation.•Revealing the significant effect of perceived content serendipity in the context of rec-vlog. Any content provider of a recommendation vlog (rec-vlog) strives to retain consumers and facilitate their continuance intention to use the rec-vlog to obtain product information. Based on dual-congruity theory and expectation-confirmation theory, our study identifies the factors explaining the generation of consumers’ continuance intention. Data collected from 513 respondents validated that consumers’ continuance intention is predicted by vlogger-consumer congruity (VCC) and perceived content diagnosticity (PCD). Moreover, VCC positively influences PCD. Our findings also reveal that perceived content serendipity (PCS) positively impacts PCD and that a higher level of PCS enlarges the effect of PCD on satisfaction. This study provides implications for both academics and practitioners.